Tren Penelitian tentang Pendidikan Sufism: Analisis Bibliometrik Publikasi Tahun 2020–2025 - Ikhwan Al Hafiz; Mastin Kustati; Bashori Bashori (Jurnal Sosial Humaniora dan Pendidikan, 2025)
This study maps global research trends, thematic structures, and the developmental trajectory of studies on Sufism education through a bibliometric analysis of  ScienceDirect -indexed publications from 2020 to 2025. Using a quantitative bibliometric approach and VOSviewer software, the analysis covers four key components: annual publication trends, keyword network structures, temporal dynamics, and research density. The findings reveal a significant shift in Sufism scholarship from classical doctrinal and historical discussions toward interdisciplinary approaches encompassing spiritual education, psychology, cultural studies, and digital religion. Four major thematic clusters emerge: spirituality and education, historical manuscripts and authority, ethics and technology, and Sufi literature. Overlay and density visualizations highlight the rise of new research directions, including ethical technology, Sufi-based psychological well-being, digital dhikr practices, and the integration of Sufism into contemporary arts and literature. The study also identifies underexplored topics such as Sufi eschatology, contemporary Sufi literature, and the intersection of Sufism with global New Age spirituality, indicating promising areas for future research.